New frontiers in technical analysis : effective tools and strategies for trading and investing - Ciana, Paul, 1983- (Hoboken, N.J. : Bloomberg Press, 2011)
"An engaging overview of today's most effective technical analysis tools and techniquesTechnical analysis helps market players predict the price behavior of a stock, commodity, or other financial instrument, giving clues about the course your trade may take in the coming weeks and months. This approach to the markets has proven itself time and again, and now, with Bloomberg on Technical Analysis, you'll discover how to put it to use in your everyday trading endeavors. Filled with in-depth insights and expert advice, Bloomberg on Technical Analysis pulls together the expertise of market professionals, analytics from Bloomberg, and the knowledge of the author himself, an experienced technical analyst who deals with traders and investors every day, to present the most up-to-date information in this field. Reviews technical indicators that traders have found to be extremely useful Taps into one of the author's great strengths: his extensive day-to-day interaction with financial professionals Contains a detailed analysis and explanation of two informative technical analysis studies performed by Bloomberg technical analysts Written with the serious trader in mind, Bloomberg on Technical Analysis offers you the tools you need to improve your performance and make the most out of your time in today's markets"--
NEW FRONTIERSIN TECHNICALANALYSIS; Contents; Preface; Acknowledgments; CHAPTER 1 Evidence of the Most Popular Technical Indicators; Defining Technical Analysis; Defining Chart Types; Evidence of Chart Type Popularity; Evidence of Technical Indicator Popularity; Applying the Most Popular Technical Indicators; Conclusion; CHAPTER 2 Everything Is Relative Strength Is Everything; "This Time It's Different"; What Is Comparative Relative Strength?; The JdK RS-Ratio and JdK RS-Momentum; Relative Rotation Graphs; Conclusion; CHAPTER 3 Applying Seasonality and Erlanger Studies.
Includes bibliographical references and index.
Print version record.
Keywords: Investment analysis; Investments; Technical analysis (Investment analysis); Investments; BUSINESS & ECONOMICS -- Finance; BUSINESS & ECONOMICS -- Investments & Securities -- General; Investment analysis; Investments; Technical analysis (Investment analysis); Investments; Electronic books